2020
DOI: 10.1002/oby.22995
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Neighborhood and Individual Socioeconomic Status, and Obesity: The Singapore Multiethnic Cohort

Abstract: It remains unclear whether ethnicity has an impact on obesity independent of socioeconomic status (SES) and environmental factors. Singapore provides a unique opportunity to address this issue because three major Asian ethnic groups are represented, and government policies prevent ethnic segregation. Therefore this study examined associations between ethnicity, SES, and obesity within neighborhoods in Singapore. Methods: Cross-sectional data from 29,819 participants of the Singapore Multiethnic Cohort who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
(50 reference statements)
4
9
0
Order By: Relevance
“…Another finding from this study indicated that, as regards ethnicity, Malays, Indians, and other Bumiputeras were at greater risk of being obese when compared with Chinese. This finding was similar to other studies conducted in Malaysia 20 and Singapore 21 and this might be due to the cultural and food preference difference among the ethnic populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another finding from this study indicated that, as regards ethnicity, Malays, Indians, and other Bumiputeras were at greater risk of being obese when compared with Chinese. This finding was similar to other studies conducted in Malaysia 20 and Singapore 21 and this might be due to the cultural and food preference difference among the ethnic populations.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in Singapore reported that obesity was higher among women, whereas lesser among men for adults aged 40 years and above. 21 This finding from this study might be due to the increase in food purchasing power and the availability of food higher in sugar content 22 as well as calorie-intensive food, along with increase in sedentary lifestyle 23 and technology attachment such as mobile devices and video games among young adults. 24 This study also indicated that adults with diabetes and hypertension were more likely to become obese.…”
Section: Discussionmentioning
confidence: 73%
“…The Singapore Multi-Ethnic Cohort (MEC) is a prospective cohort study of environmental, lifestyle, and genetic determinants of non-communicable diseases, with regular, ongoing participant re-visits, comprising health screenings and interviewer-administered questionnaires [ 35 , 36 ]. Detailed information about this study can be found on the study website [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…After fieldwork, we obtained building age from lease commencement year data obtained from the Singapore Land Authority [24,25], and median house price per public apartment block was used as a proxy for the socioeconomic status (SES) of its residents and valued at its resale price attained through a government website (https://data.gov.sg) [26], since building age and SES [27][28][29][30] have previously been found to be correlated with mosquito abundance.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%